A Comparative Study of Enabling Technologies for Autonomous Vehicles - BhavyaShree, P; Takri, Sharon Thomas; Gurunath, R (International Journal of Computer Sciences and Engineering, 2025)
Autonomous driving technology is an upcoming and fast developing, and a future business booster in the automotive, smart cities, transportation, and other related sectors. The better usage of the concepts such as Artificial Intelligence and Machine learning in the field of automotive industry is a promising one. Certain automobile companies are investing billions of money on research and development of self-driving vehicles. In this paper the author broadly discuss about the autonomous vehicles and their working functionalities, adding to that, the pros and cons of LiDAR technology behind every autonomous vehicles. This paper also throws light on other enabling technology such as GPS, Video Camera, Radar, Position Estimator and Distance Sensors and compare with LiDAR technology.